PENGARUH KOMPETENSI, EFIKASI DIRI (SELF EFFICACY), DAN KUALITAS KEHIDUPAN KERJA (QUALITY OF WORK LIFE) TERHADAP KINERJA PEGAWAI PERUSAHAAN DAERAH AIR MINUM (PERUMDAM) TIRTA MAHAMERU LUMAJANG - Rommy Wahyu Hidayat; Dianawati Suryaningtyas; Andi Nu Graha (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the impact of competence, self-efficacy, and quality of work life on employee performance at Perumdam Tirta Mahameru Lumajang. This study relies on primary quantitative data specifically for permanent employees, with a sample of 50 permanent staff members. Data collection was conducted using a questionnaire that applies a Likert scale. To analyze the data, a multiple linear regression method was used through SPSS software. The results of the study indicate that competence, self-efficacy, and quality of work life simultaneously have a significant positive influence on employee performance at Perumdam Tirta Mahameru Lumajang. When viewed individually, competence and quality of work life show a positive and significant influence on employee performance, while self-efficacy has a positive impact although not significant. These findings suggest that to increase employee confidence and belief, the company should include additional factors through training programs to strengthen competencies in each division, as well as increase self-confidence through soft skills and hard skills training. Thus, it is expected that employee self-efficacy can increase and have a more significant impact on the overall performance of Perumdam Tirta Mahameru Lumajang. Keywords : Competence, Self Efficacy, Quality of Work Life, Employee Performance.